2013
DOI: 10.1108/s0897-3016(2013)0000021011
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Employee Involvement Practices: Organizational Change Issues and Insights

Abstract: Employee involvement (EI) as part of a set of high performance work system (HPWS) has successfully transformed a large number of organizations and become standard practice many new organizations today. Despite the proven benefits of EI, however, it is still not as common as it could be even when accounting for industry and organization differences. We suggest that EI implementation is limited in part by challenges of change management. We review the recent research on EI and HPWS and suggest way in which chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…Applicability and design of self-organised teams Self-organised teams are not suited for all organisations; and they have produced mixed results in respect to employee behavioursuch as higher turnover and absenteeism (Kirkman et al, 1999;Benson et al, 2013). Such mixed outcomes might be associated with organisations that have limited resources do not devote sufficient time to training, coaching, and supervision of a newly formed self-organised teams.…”
Section: Self-organised Teams and Agile Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Applicability and design of self-organised teams Self-organised teams are not suited for all organisations; and they have produced mixed results in respect to employee behavioursuch as higher turnover and absenteeism (Kirkman et al, 1999;Benson et al, 2013). Such mixed outcomes might be associated with organisations that have limited resources do not devote sufficient time to training, coaching, and supervision of a newly formed self-organised teams.…”
Section: Self-organised Teams and Agile Leadershipmentioning
confidence: 99%
“…Employees whose tasks are centred on low-level routine activities or tasks of a repetitive nature may achieve higher productivity under a traditional leadership model (Batt, 1999); and that time spent in training and quality circles (group problem-solving) decreases productivity, at least in the short term (Benson et al, 2013;Goncalves, 2006). Research by Erez et al (2002) showed that self-organised teams have resulted in mixed effectiveness depending on environmental circumstances (Herre, 2010); and indicated that use of peer evaluations and rotating leadership roles promoted better workload sharing and cooperation.…”
Section: Ijppm 641mentioning
confidence: 99%
“…In the introduction, we mentioned several factors associated with the success and sustainability of the improvement programmes, including creating understanding and motivation, establishing and communicating a vision and strategy, committed leadership, involving employees in change activities, creating short-term wins and alignment with the value system (e.g. Appelbaum et al, 2012;Beer & Nohria, 2000;Benson et al, 2013;Burnes, 2011;Kettinger & Grover, 1995;Kotter, 1995). We were able to identify all the factors mentioned above in our present case study.…”
Section: Discussionmentioning
confidence: 99%
“…A number of prescriptions on how to manage improvement programmes exist, such as creating understanding and motivation, establishing and communicating a vision and strategy, committed leadership, involving employees in change activities, creating short-term wins and alignment with the value system (e.g. Appelbaum, Habashy, Malo, & Shafiq, 2012;Beer & Nohria, 2000;Benson, Kimmel, & Lawler, 2013;Burnes, 2011;Canning & Found, 2015;Higgs & Rowland, 2011;Kettinger & Grover, 1995;Kotter, 1995). In the literature, these prescriptions are often presented as general recommendations for any particular organisational change initiative.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst part of the literature has argued that, if not managed properly, EI may reinforce power asymmetries between privileged groups and minorities, thus nurturing discriminatory practices at work (Constant et al, 2009), it is expected to lower the perceived fear and uncertainty associated with organizational transition (Sahoo, 2014). Increased EI implies the establishment of positive sensations with OC (Sharma and Venkateswaran, 2020), that foster ethical conducts during the transition process and, consequently, reduce the risks of unfair treatment and discrimination (Benson et al, 2013;Sharif and Scandura, 2014). In addition, EI discourages OC cynicism (Brown and Cregan, 2008) and improves interpersonal relations during processes of change (Palumbo et al, 2017).…”
Section: Preventing the Side Effects Of Organizational Change On Discriminationmentioning
confidence: 99%